PENERAPAN MANAJEMEN PEMBELAJARAN DI SEKOLAH DASAR SELAMA PANDEMI - Umi Rahmawati, Dwi Nur; Puspita, Ratna Dewi (UIN Imam Bonjol Padang, 2020)
This study aims to reveal how far learning management is carried out by teachers in schools and how learning management is implemented by teachers during the pandemic. This research is Mixed Method research with a sequential explanation method. Samples were taken using a purposive sampling technique. Data collection techniques used questionnaires and data analysis using statistics as an analysis technique followed by interviews and documentation then validated the findings with the Member Checking strategy. The results of statistical analysis of the implementation of learning management based on the function of learning management which includes planning, organizing, mobilizing, and monitoring during the pandemic are categorized as